1999
DOI: 10.1097/00005650-199901000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Suggesting That a Chronic Disease Self-Management Program Can Improve Health Status While Reducing Hospitalization

Abstract: An intervention designed specifically to meet the needs of a heterogeneous group of chronic disease patients, including those with comorbid conditions, was feasible and beneficial beyond usual care in terms of improved health behaviors and health status. It also resulted in fewer hospitalizations and days of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
1,548
7
28

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,947 publications
(1,668 citation statements)
references
References 8 publications
42
1,548
7
28
Order By: Relevance
“…31 Self management approaches also use peer leaders, which would address the importance of mentors identified in this study. Self management approaches have been used with patients with arthritis and diabetes, 32,33 but to our knowledge, have not been used with people with SCI. Any approach to education, however, needs to focus on the topics of most importance to people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…31 Self management approaches also use peer leaders, which would address the importance of mentors identified in this study. Self management approaches have been used with patients with arthritis and diabetes, 32,33 but to our knowledge, have not been used with people with SCI. Any approach to education, however, needs to focus on the topics of most importance to people with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…If self-management is to be of use in hypertension, there may therefore be a need both to promote selfmonitoring and then also further steps to encourage individuals to use the results of that monitoring to improve the control of their condition. In a trial of an educational 'chronic disease self-management programme' aimed at a group of 952 subjects with a variety of chronic diseases, Lorig et al 17 showed that their intervention improved health behaviours and health status, and reduced hospitalisations, during 6 months of follow-up. Again, long-term benefits are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, participants in any one program have a variety of chronic conditions. In a randomized study, participants (n ϭ 952) with arthritis, heart disease, lung disease, or stroke were all placed together in the same 14-hour, peerled intervention (12). Outcome data suggest that intervention participants, when compared with randomized controls at 6 months, significantly improved their selfmanagement behaviors, improved their health status (role activities, health distress, disability, and fatigue), improved their self efficacy, and decreased the number of days in the hospital (P Ͻ 0.05) (12).…”
Section: Background the Arthritis Self-management Programmentioning
confidence: 99%
“…Unlike the ASMP, the CDSMP is a generic program that individuals with many different types of chronic conditions attend at the same time. In an initial randomized study, persons with arthritis who attended the CDSMP workshop showed improvements in health behaviors and health status (12). Both the ASMP and the CDSMP are large programs in the United States, Great Britain, Australia, New Zealand, and Canada.…”
Section: Introductionmentioning
confidence: 99%